CIRP Encyclopedia of Production Engineering - Chatti, Sami.; Laperrière, Luc.; Reinhart, Gunther; Tolio, Tullio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2019)
This high quality reference work has been written and reviewed by members of The International Academy for Production Engineering, also known as CIRP. This Academy is recognized worldwide to represent the highest standards in research on production engineering, which includes design, optimization, control, management of processes, machines, and systems. One key concept behind this Encyclopedia is that apart from covering fundamental concepts in the field of production engineering, it also closely follows recent developments and emerging concepts. In particular this renewed print edition covers a wide range of new topical entries such as Hybrid Processes, High Performance Grinding, Biomimetic Design, Cold Spray, Sheet-bulk Metal Forming, Ecodesign, Cyber Physical System, Nano Technology, or Geometrical Product Specification. The second edition also comprises reviewed entries from the first version, which have been updated to reflect new standards or developments. The target audience primarily comprises researchers, engineers, managers, graduate students, and many others whose day-to-day work gravitates around production engineering technologies in the global market.
Abrasive Processes -- Assembly -- Cutting -- Design -- Electrophysical and Chemical Processes -- Forming -- Life Cycle Engineering -- Machines -- Precision Engineering and Metrology -- Production Systems and Organizations -- Surfaces.
Keywords: Industrial engineering; Production engineering; Production management; Computer-aided engineering; Chemistry, Technical; Industrial and Production Engineering; Operations Management; Computer-Aided Engineering (CAD, CAE) and Design; Industrial Chemistry